Plasma concentrations of ascorbic acid in a cross section of the German population. Issue 1 (January 2018) - Hagel, Alexander F.; Albrecht, Heinz; Dauth, Wolfgang; Hagel, Wolfgang; Vitali, Francesco; Ganzleben, Ingo; Schultis, Hans W.; Konturek, Peter C.; Stein, Jürgen; Neurath, Markus F.; Raithel, Martin
Objectives: Vitamin C deficiency is considered extremely rare in modern industrialized countries. This study was performed to assess vitamin C concentrations in the German population. Methods: As part of a consultant–patient seminar on nutrition and food intolerances, patients were asked to participate in this study on a voluntary basis. Blood samples were taken for analysis of serum vitamin C concentrations, and all patients were asked to complete a questionnaire. The vitamin C concentration was determined by high-performance liquid chromatography. Results: Of approximately 300 patients attending the seminar, 188 (62.6%) consented to vitamin C blood sample analysis and 178 (59.3%) answered the questionnaire. The mean vitamin C concentration was 7.98 mg/L (range, 0.50–17.40; reference range, 5–15 mg/L). A low plasma level with vitamin C insufficiency (<5 mg/L) was found in 31 patients (17.4%), and a potential scorbutogenic deficiency (<1.5 mg/L) was found in 6 (3.3%). Conclusions: Potential vitamin C insufficiency and deficiency is common. It is therefore possible, even in modern developed populations, that certain individuals may require a higher intake of vitamin C.